Roundtable: The conservation and sustainable use of Neglected and Underutilized Species (NUS) in Ghana - Highlights - Vernooy, Ronnie; Nyadanu, Daniel (2021)
As part of a development initiative "The potential of agrobiodiversity for improving diets and nutrition in Ghana" to contribute to the transformation of food systems for healthy and sustainable diets and environmental sustainability, a Roundtable on the conservation and sustainable use of NUS in Ghana was organized in Accra on 28 October 2021, with participation of representatives of government institutions, private sector entities, and civil society organizations